316 Frontal-cerebellar EEG source localization and functional connectivity as predictors of Alzheimer's disease-related cognitive decline. (April 2022) - Paitel, Elizabeth R.; Nielson, Kristy A.
Abstract : OBJECTIVES/GOALS: Novel EEG source localization and functional connectivity will assess frontal and cerebellar activity as predictors of subsequent memory and executive functioning (EF) decline in healthy, asymptomatic older adults who carry the Apolipoprotein-E Îµ4 allele (Îµ4+), which conveys up to 12x increased risk for Alzheimers disease (AD). METHODS/STUDY POPULATION: Healthy, cognitively intact Îµ4+ older adults (n = 23; ages 65-89) completed neuropsychological testing (focus on memory and EF) and EEG at Time 1, returning an average of one year later for neuropsychological retesting. EEG data during successful stop-signal inhibitory control trials will be used for advanced source localization and functional connectivity, with a focus on frontal and cerebellar regions of interest (ROIs). Source analyses will focus on the N200 time window ( 200-350ms) to assess conflict processing and P300 ( 300-550ms) for performance evaluation. Connectivity analyses are frequency-based, and will focus on theta band connectivity to assess conflict processing and delta to assess performance evaluation. RESULTS/ANTICIPATED RESULTS: Using hierarchical linear regression models, the magnitude of source activation within ROIs and connectivity metrics between ROIs will be used to predict residualized change in memory and executive function metrics between Time 1 and Time 2. We anticipate that 1) greater, compensatory activation in frontal ROIs during the N200 window, and 2) less cerebellar activation during P300, will predict memory and executive decline over the retest interval. Decline will also be predicted by 3) greater inter-hemispheric frontal connectivity in the theta band (conflict processing) and 4) less frontal-cerebellar delta connectivity (performance evaluation). DISCUSSION/SIGNIFICANCE: At most, 50% of Îµ4 carriers will develop AD. Thus, identifying which carriers will decline is crucial to enabling successful, early intervention. Cerebellar dysfunction and impaired connectivity may be among the earliest indicators of incipient AD. Cutting-edge cerebellar EEG may enable an accessible option for early discernment of AD risk.